The trigger - Clarke, Arthur C. 1917-2008; Kube-MacDowell, Michael P. (Bantam Books, 1999)
A scientist discovers a device that detonates explosives, in bullets and bombs. The device, Trigger, is thus able to do away with gunpowder-based weapons, but can it be allowed? The gun lobby and the army want it banned and a pro-Trigger senator is assassinated.
Keywords: Technology -- Fiction; Weapons -- Control -- Fiction; Science fiction